Angular‐Resolved Magnetometry Beyond Triclinic Crystals Part II: Torque Magnetometry of Cp*ErCOT Single‐Molecule Magnets. Issue 43 (11th September 2014) - Perfetti, Mauro; Cucinotta, Giuseppe; Boulon, Marie‐Emmanuelle; El Hallak, Fadi; Gao, Song; Sessoli, Roberta
Abstract: The experimental investigation of the molecular magnetic anisotropy in crystals in which the magnetic centers are symmetry related, but do not have a parallel orientation has been approached by using torque magnetometry. A single crystal of the orthorhombic organometallic Cp*ErCOT [Cp*=pentamethylcyclopentadiene anion (C5 Me5 − ); COT=cyclooctatetraenedianion (C8 H8 2− )] single‐molecule magnet, characterized by the presence of two nonparallel families of molecules in the crystal, has been investigated above its blocking temperature. The results confirm an Ising‐type anisotropy with the easy direction pointing along the pseudosymmetry axis of the complex, as previously suggested by out‐of‐equilibrium angular‐resolved magnetometry. The use of torque magnetometry, not requiring the presence of magnetic hysteresis, proves to be even more powerful for these purposes than standard single‐crystal magnetometry. Furthermore, exploiting the sensitivity and versatility of this technique, magnetic anisotropy has been investigated up to 150 K, providing additional information on the crystal‐field splitting of the ground J multiplet of the Er III ion. Abstract : From crystal to molecule : Extracting information on the molecular magnetic anisotropy from single crystals, in which the magnetic centers exhibit more than one orientation, is not straightforward, but is often necessary in molecular magnetism. Torque magnetometry, employed on an organometallic single‐molecule magnet, is found to be significantly more powerful than standard magnetometry, as well as being more generally applicable and significantly more sensitive (see figure).